Developing a nursing healthcare protocol: a case report - Talita Wérica Borges Figueiredo; Nen Nalú Alves das Mercês; Maria Ribeiro Lacerda; Ana Paula Hermann
ABSTRACT Objective: to report the use experience of convergent healthcare research for developing a nursing care protocol. Method: convergent care research developed in university hospital, from July to December 2016, with 27 participants. Results: the stages of the research and its results are described in the steps: conception, instrumentation, screening and analysis. The end result was the nursing care protocol in day zero of hematopoietic stem cell transplantation. Conclusion: convergent care research was an appropriate method for developing the care protocol, and an important contribution to the approximation between theory and practice. The nursing care protocol was the result of this study and confirmed both the purpose of the research as a professional Master's in acquiring knowledge aimed at improving professional practice.